Treatment of rape victims by the Ethiopian criminal justice system in the contemporary period: A critical legal-victimological analysis - Chanko Enga Cheru; Halder Debarati (Temida)
The treatment of rape victims within the framework of Ethiopian criminal law is critically explored in this paper, with a particular focus on the Criminal Code of Ethiopia (2004). While Ethiopia has long recognised rape as a criminal offence, dating back to the Fetha Negest in the 13th century, earlier legal frameworks were more concerned with preserving family honour than delivering justice for female victims. The Criminal Code marked an important step forward by offering a more nuanced definition of rape. Yet, it still fails to address significant issues, such as marital rape and the sexual exploitation of minor girls. Although the Code provides some protections for rape survivors, including legal and medical assistance, the article highlights a crucial gap in addressing the emotional and psychological consequences of rape. It argues for a more victim-centred approach to justice in Ethiopia, advocating for the introduction of victim impact statements to ensure a more comprehensive response to rape.